A Critical Look At Trauma-Informed Care Among Agencies and Systems Serving Maltreated Youth and Their Families. (May 2016) - Hanson, Rochelle F.; Lang, Jason
The past two decades have witnessed an increase in programs targeting children and youth impacted by traumatic events, with a heightened focus on ensuring that all such programs and relevant service systems are trauma informed. While such efforts are laudable, trauma-informed care (TIC) is defined in a number of ways, limiting evaluation of these initiatives, specifically as they relate to the potential for improved outcomes or reduced costs often used to advocate for TIC. Widespread interest in TIC, despite an apparent dearth of empirical research, served as the impetus for this special section. Our goal was to identify the most rigorous empirical studies available. These six papers were selected based on their inclusion of a definition of TIC, focus on at least one component of TIC in a child-serving system, and availability of empirical data demonstrating the effectiveness of their efforts. In addition to introducing these papers, we share preliminary data from a brief, anonymous survey of child-serving professionals across various systems and roles to obtain feedback about definitional and conceptual issues related to TIC. While this special section provides a representation of available empirical work, significant gaps between research and practice of TIC remain, with important implications for future work.